Nasopharyngeal virome analysis of COVID‐19 patients during three different waves in Campania region of Italy. Issue 5 (15th January 2022) - Ferravante, Carlo; Sanna, Giuseppina; Melone, Viola; Fromentier, Aurore; Rocco, Teresa; D'Agostino, Ylenia; Lamberti, Jessica; Alexandrova, Elena; Pecoraro, Giovanni; Pagliano, Pasquale; Astorri, Roberta; Manzin, Aldo; et al.
Abstract: From December 2019, severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection has spread rapidly, leading to a global pandemic. Little is known about possible relationships between SARS‐CoV‐2 and other viruses in the respiratory system affecting patient prognosis and outcomes. This study aims to characterize respiratory virome profiles in association with SARS‐CoV‐2 infection and disease severity, through the analysis in 89 nasopharyngeal swabs collected in a patient's cohort from the Campania region (Southern Italy). Results show coinfections with viral species belonging to Coronaviridae, Retroviridae, Herpesviridae, Poxviridae, Pneumoviridae, Pandoraviridae, and Anelloviridae families and only 2% of the cases (2/89) identified respiratory viruses. Key Points: The severe acute respiratory syndrome coronavirus 2 infection is considered a major global threat that is still spreading around the world. Nasopharyngeal swabs samples were collected from the Campania region cohort of 89 Covid‐19 patients. Descriptive analysis of respiratory virome was carried out with the HOME‐BIO pipeline, that performed viral taxonomy profiling. It detected coinfections with viral species belonging to Coronaviridae, Retroviridae, Herpesviridae, Poxviridae, Pneumoviridae, Pandoraviridae, and Anelloviridae family. Only 2% of the cases (2/89) identified respiratory viruses.